Irradiated Skeletal Muscle Cells Mimicking Those of Atypical Fibroxanthoma on Mohs Frozen Sections. (May 2021) - Xiong, Michael Y.; Kolker, Steven; Bennett, Richard G.
Abstract : Abstract: Radiation can induce changes to skeletal muscle cells that may mimic and thus be confused with cells of atypical fibroxanthoma (AFX), pleomorphic dermal sarcoma, spindle cell squamous cell carcinoma, and other spindle soft-tissue tumors. An 80-year-old White man presented for Mohs micrographic surgery of an AFX on the left lateral neck. The medical history was notable for a tongue squamous cell carcinoma 9 years before that had been treated with wide local excision, left neck dissection, and radiation to the oral cavity and left neck. Frozen sections from the first stage of Mohs did not show typical AFX, but did reveal patchy clusters of atypical spindled and epithelioid cells, some with multiple nuclei. Because of the unusual appearance of these cells, Mohs micrographic surgery was halted, and the frozen tissue block was sent for permanent pathology examination. The cells on permanent sections stained positive for desmin, revealing them to be of skeletal muscle origin (in this case damaged platysma muscle because of late postradiation changes). It is thus important for the Mohs surgeon and the consultant dermatopathologist to be aware of the unusual histologic appearance of irradiated skeletal muscle to avoid confusion with other spindle cell tumors.